Peran Citra Merek, Store Atmosphere dan Word Of Mouth dalam Meningkatkan Keputusan Pembelian Konsumen - Nuraini Laila Luthfiah; Iim Takwim; Irfan Dzulfiqar (Journal of Management and Bussines (JOMB), 2023)
This study aims to find out the factors that can improve purchasing decisions by looking at the role of brand image, store atmosphere and word of mouth. The research method used is a quantitative approach to the survey by distributing questionnaires to respondents. This method is used to understand the impact of each variable. The results of this study indicate that purchasing decisions are positively influenced by brand image, store atmosphere and word of mouth. Thus the hypothesis proposed in this study can be accepted. In conclusion, this research has implications for business people, especially business owners to improve the image and store atmosphere better so that consumers feel comfortable when visiting. Keywords: Brand Image, Purchase Decision, Store Atmosphere, Word Of Mouth